Sinonasal symptoms in migraine without aura: results from the cross-sectional ‘Migraine in Poland’ study - Straburzynski, Marcin; Nowaczewska, Magdalena; Czapinska-Ciepiela, Ewa K.; Gryglas-Dworak, Anna; Budrewicz, Slawomir; Waliszewska-Prosół, Marta (Frontiers in Neurology, 2023)
Background: Migraine without aura (MwoA) is often mistaken for rhinosinusitis. The purpose of this study was to assess the prevalence of sinonasal symptoms, sinusitis-targeting medication use and burden of migraine in a large group of people with MwoA attacks accompanied by rhinologic symptoms. Methods: Data was collected in a cross-sectional online survey based on an adapted population-based study questionnaire. The analysis included the prevalence of rhinorrhea, mucopurulent nasal discharge, nasal congestion, facial pressure and tenderness to palpation, hyposmia/anosmia and osmophobia. Results: 1679 (52.73%) MwoA people were identified among 3225 respondents (women n = 2809, 87.10%) aged 13-80 years (median age 39; standard deviation 10.4). 1004/1679 (59.8%) migraine patients reported one or more rhinologic symptoms and 341/1679 (20.3%) MwoA respondents had symptoms that met rhinosinusitis clinical diagnostic criteria during their headache attacks. In migraine patients, osmophobia was associated with hyposmia (n = 141 (12.7%) vs n = 41 (7.2%); p = 0.001) and a sensation of unpleasant smells (n = 216 (19.4%) vs n = 45 (8.5%); p = 0.001), while facial tenderness to palpation was associated with facial allodynia (n = 532 (50.4%) vs n = 211 (33.9%); p < 0.001). People with migraine accompanied by rhinosinusitis-like symptoms experienced more disease burden and used ‘sinus medications’ more often. Conclusions: MwoA patients with rhinosinusitis-like symptoms during migraine attacks require cautious assessment, especially that some symptoms seem to have little value in distinguishing between these disorders (i.e. facial tenderness, hyposmia), while many of these patients have a greater disease burden and therefore often choose medications targeting rhinologic instead of neurologic mechanisms.